Endoscopic, endonasal decompression of spinal stenosis with myelopathy secondary to cranio-vertebral tuberculosis: Two cases - Puraviappan, P.; Tang, I.P.; Yong, D.J.; Prepageran, N.; Carrau, R.L.; Kassam, A.B. (Cambridge University Press, 2010)
Background: Tuberculosis can cause extensive osseo-ligamentous destruction at the cranio-vertebral junction, leading to atlanto-axial instability and compression of vital cervico-medullary centres. This may manifest as quadriparesis, bulbar dysfunction and respiratory insufficiency. Aim: We report two patients presenting with spinal stenosis and cord compression secondary to cranio-vertebral tuberculosis, who were successfully decompressed via an endoscopic, endonasal approach. Study design: Two case reports. Methods and results: Both patients were successfully decompressed via an endoscopic, endonasal approach which provided access to the cranio-vertebral junction and upper cervical spine. Conclusion: An endoscopic, endonasal approach is feasible for the surgical management of cranio-vertebral junction stenosis; such an approach minimises surgical trauma to critical structures, reducing post-operative morbidity and the duration of hospital stay.